Pengembangan Media Pembelajaran GURICA (Game Edukasi Ular Tangga Operasi Hitung Pecahan) Di Sekolah Dasar - Novika Dian Pancasari Gabriela; Indri Anugraheni (Peneliti.net, 2022)
This study aims to develop Mathematics learning media for 5 graders of elementary school, namely GURICA (Educational Game Snakes and Ladders Operation Counting Fractions). GURICA is a game application consist of fun arithmetic addition and subtraction operations for grade 5 of Elementary School. This study applies research and development (R&D) that uses the ASSURE development model. The data collection technique which is used in this development is a observations, interviews and questionnaires. The data analysis technique used in this research is descriptive technique. Based on the research, there are three validity points being assessed. The first is the material experts, which shows 92,00% which were in the very high. Second is media experts, with 90,00% as a result which considered high as well. And last is teacher response which obtains 89,14% result which is high also. The results of the validity test show that the development of the GURICA media (Educational Game Snakes and Ladders Operations Counting Fractions) is proven to be valid in learning mathematics for grade 5 Elementary School.